2012
DOI: 10.1007/s00203-012-0823-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic lipopeptide profile of the plant-beneficial endophytic bacterium Bacillus subtilis HC8

Abstract: In a previous study (Malfanova et al. in Microbial Biotech 4:523–532, 2011), we described the isolation and partial characterization of the biocontrol endophytic bacterium B. subtilis HC8. Using thin-layer chromatography, we have detected several bioactive antifungal compounds in the methanolic extract from the acid-precipitated supernatant of HC8. In the present study, we have further analyzed this methanolic extract using liquid chromatography-mass spectrometry. Based on the comparison of retention times and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 27 publications
3
54
0
1
Order By: Relevance
“…Bacillus subtilis is a common soil and rhizosphere resident bacteria having dual beneficial properties of plant growth promotion as well as biocontrol activities [11,12]. Almost 5% of its genome is devoted for the production of antibiotics and many strains from this genus have shown the potential to produce about two dozen structurally diverse antimicrobial compounds [11][12][13]. Most active and useful among these compounds are the cyclic lipopeptides of three families: surfactin, iturin and fengycin.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus subtilis is a common soil and rhizosphere resident bacteria having dual beneficial properties of plant growth promotion as well as biocontrol activities [11,12]. Almost 5% of its genome is devoted for the production of antibiotics and many strains from this genus have shown the potential to produce about two dozen structurally diverse antimicrobial compounds [11][12][13]. Most active and useful among these compounds are the cyclic lipopeptides of three families: surfactin, iturin and fengycin.…”
Section: Introductionmentioning
confidence: 99%
“…Tarkka and Hampp (2008) and Prapagdee et al (2008) reported the role of extracellular secondary metabolites of soil bacterium Streptomycetes in biotic interaction with the host plants. Likewise, the compounds mycosubtilin, rhizocticins, antifungal phosphonate oligopeptides and cyclic lipopeptide produced by different strains of B. subtilis enhanced the organism's antagonistic and plant growth promotion activities (Leclère et al 2005;Borisova et al 2010;Malfanova et al 2012). Vinale et al (2008) reported Trichoderma species to be well known producers of compounds that substantially affect the metabolism of the plant.…”
Section: Resultsmentioning
confidence: 99%
“…The composition of amino acids in the molecule is determined by paper chromatography and automatic amino acid analyzer. Methyl esterification is conducted first before fatty acid structure measurement, followed by research with NMR (Nuclear Magnetic Resonance) and mass spectrometry instruments [10,11].…”
Section: Lipopeptide Structure Identificationmentioning
confidence: 99%
“…Lipopeptides were eluted using a two component solvent system of which solvent A is water and solvent B is acetonitrile, both acidified with 0.1% formic acid. We used four different elution programs including one general program to elute all lipopeptides and three family-specific programs to get a better separation and quantification of the different lipopeptides within each family [10].…”
Section: Quantitative Analysis Of Lipopeptidesmentioning
confidence: 99%